Critical Reading within the Framework of Kasepuhan Banten Kidul Tradition - Mualimah, Eka; Mulyati, Yeti; Sastromihardjo, Andoyo; Damayanti, Vismaia S.; Salim, Agus (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The research seeks to examine how critical reading practice are embedded whithin the eveyday life of the Kasepuhan Banten Kidul indigenous community. Employing a qualitative approach through an exploratory study design, the study investigates the meanings and critical thinking processes that emerge organically and contextually in the community's sociocultural setting. Date were obtained through participatory observation. in-depth interviews, and documentation, and subsequently analyzed using thematic analysis. The findings indicate tahat the local traditions of Kasepuhan Banten Kidul not only serve to preserve cultural heritage but also function as a discursive space that cultivates critical reasoning, particularly in decision-making, the transmission of moral values, and the interpretation of daily events